Synthesis and Crystal Structure of [Cu2(TTA)4·(4,4'-bpy)] - Jiang, Guang-Qi; Lu, Yong-Zhong; Li, Xian-Ling; Wei, Ran-Shi; Shao, Lin (Asian Journal of Chemistry, 2013)
A new complex, [Cu2(TTA)4·(4,4'-bpy)] (TTA = 2-thenoyl-trifluoracetone, bpy = bipyridine) with the molecular formula C42H28N2O8S4F12Cu2 has been synthesized and structurally characterized by elemental analysis, IR spectrum and X-ray diffraction analysis. The crystal belongs to triclinic system, P-1 group with unit cell parameters: a = 8.5755(7) Å, b = 10.2215(8) Å, c = 13.9964(12) Å, a = 72.548 (3)º, b = 85.407 (3)º, g = 86.130 (3)º. V=1165.4 (17) Å3, Z = 1, Mr = 1172.04, Dc = 1.6700 (2) g/cm3, μ = 1.193 mm-1, F (000) = 588.0, R = 0.0601, wR = 0.1889 for 4044 reflections with I > 2s (I).